CONVERTING INFIX NOTATION TO POSTFIX NOTATION USING STACK APPLICATION IN DATA STRUCTURE - Arianty, Rini (Universitas Gunadarma, 2008)
The use of stack becomes a common issue for memory address assignment, placement in data space, and other applications. As a part of data structure, stack application is also used for different needs, such as matching parentheses and conversion from Infix notation into Postfix. This paper was written to provide approach in the conversion process form Infix to Postfix in arithmetics.Keyword(s): Arithmetic, Infox notation, Postfix notation, Stack, Data structure.Subject Description : E.Data | E.1.Data Structures | Lists, stacks and query